Supply Chain Performance Improvement Strategy through Quality of Synergy in the Automotive Components Industry - Purwani, Tri; Nurcholis, Lutfi (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2016)
The purpose of this study were 1) develop a new concept of Bilateral Symmetry, which is the ability of similarity based on transparency and standardization, 2) conduct empirical testing and analyzing the effect of bilateral symmetry to the improved supply chain performance through quality of synergy in industrial automotive components. The study population includes the entire automotive component industry in Indonesia. This study used sample of 105 respondents using purposive sampling method to comply with the AMOS program. The study result shows that the ability of similarity standardization and the ability of the similarity of transparency have positive significant impact on the quality of synergy, and quality of synergy have positive significant impact on the supply chain performance. In addition, from the results of hypothesis testing found two strategies that can improve supply chain performance with 1) increasing the ability of similarity standardization and 2) improve transparency through quality of synergy.Tujuan dari penelitian ini adalah mengembangkan konsep baru bilateral symmetry, yang merupakan kemampuan kesamaan berdasarkan transparansi dan standarisasi, dan melakukan pengujian empiris dan menganalisis pengaruh simetri bilateral untuk peningkatan kinerja rantai pasokan melalui kualitas sinergi pada komponen otomotif industri. Populasi penelitian meliputi seluruh industri komponen otomotif di Indonesia. Penelitian ini menggunakan sampel 105 responden dengan menggunakan metode purposive sampling dan dianalisis dengan program AMOS. Hasil penelitian menunjukkan bahwa kemampuan kesamaan standarisasi dan kemampuan kesamaan transparansi berdampak signifikan positif pada kualitas sinergi, dan kualitas sinergi berdampak signifikan positif terhadap kinerja rantai pasokan. Selain itu, dari hasil pengujian hipotesis menemukan dua strategi yang dapat meningkatkan kinerja supply chain dengan meningkatkan kemampuan kesamaan standarisasi dan meningkatkan transparansi melalui kualitas sinergi.